Design construction and testing of a livestock loading and unloading ramp (2010)
Loading and unloading constitute major aspects of livestock transportation. In many circumstances, they are accomplished with a lot of drudgery and harm to both the livestock and handler. More friendly handling methods are desirable. A simple wooden ramp was designed and constructed at the dairy unit of the teaching and research farm of the University of Ibadan. The ramp was tested by loading cattle into a trailer while observing any physical damage and consolidation movement of the columns. The integrity of the structure was maintained while no consolidation movement was observed. Animal exhibited reluctance during loading but unloaded with ease. An extended curved race and screening are desirable in order to derive maximum benefits from the use of the ramp. Tests of longer duration should form the thrust of future work.